Zapożyczenia tureckie w gwarach polskich - Kostecka -Sadowa, Anna (Slavia Occidentalis, 2015)
The analysis of the material included in the Dictionary of Polish Local Dialects (DPLD) to present their geographical scopes in Polish local dialects; to show the degree to which they have been adopted by local dialects – both from the formal and the semantic point of view; to show the way they function in the local dialects; to group the borrowings into semantic fields and to present the way they function within the separated meaning groups. The presented material shows that the degree of intensity of Russian borrowings in particular semantic fields is varied. The largest amount of borrowings are names defining a man with reference to his physical and psychological features, as well as other features related to physical appearance. A little smaller semantic group includes the names of plants and animals. The language adopted specific names, often characteristic of the folk culture, which were related to practical everyday life. Such borrowings refer to the names of tools, vessels and objects typical of the life of the village. It is on the basis of such everyday life on the border that practical Polish and East Slavic relations developed. In quite a natural way, those relations caused language interference which resulted in the borrowings that are known even now. The presented material shows that the degree of intensity of Russian borrowings in particular semantic fields is varied.